2022
DOI: 10.3390/vaccines10020155
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Secreted Protease/Anti-Protease Balance as a Vaccine Strategy against the Helminth Fasciola hepatica

Abstract: The liver fluke Fasciola hepatica is an economically important global pathogen of humans and their livestock. To facilitate host invasion and migration, F. hepatica secretes an abundance of cathepsin peptidases but prevents excessive damage to both parasite and host tissues by co-secreting regulatory peptidase inhibitors, cystatins/stefins and Kunitz-type inhibitors. Here, we report a vaccine strategy aimed at disrupting the parasite’s protease/anti-protease balance by targeting these key inhibitors. Our vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Previously characterised F. hepatica sequences identified as cathepsin L peptidases, cathepsin B peptidases, legumain, Kunitz-type inhibitors, serine protease inhibitors (serpins) and stefins/cystatins from the following studies [ 4 , 5 , 7 , 9 , 12 ] were used as reference sequences for BLASTp analysis to (a) confirm the sequences within the F. hepatica genome, and (b) identify homologous sequences within the stage-specific F. gigantica transcriptome datasets (PRJNA350370). The in silico descriptive annotations of the gene transcripts in the specific datasets were also screened.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously characterised F. hepatica sequences identified as cathepsin L peptidases, cathepsin B peptidases, legumain, Kunitz-type inhibitors, serine protease inhibitors (serpins) and stefins/cystatins from the following studies [ 4 , 5 , 7 , 9 , 12 ] were used as reference sequences for BLASTp analysis to (a) confirm the sequences within the F. hepatica genome, and (b) identify homologous sequences within the stage-specific F. gigantica transcriptome datasets (PRJNA350370). The in silico descriptive annotations of the gene transcripts in the specific datasets were also screened.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic studies of the molecules released by the F. hepatica stages in the mammalian host, termed excreted-secreted (ES) products, found that a large proportion of these host interacting proteins were comprised of highly proteolytic cathepsin cysteine peptidases (reviewed by [ 4 ]). Further studies revealed that the activity of these peptidases is strictly regulated by the co-release of a variety of cognate peptidase inhibitors, namely Kunitz-type inhibitors, and stefins/cystatins [ 5 , 6 , 7 ]. In addition to regulating the parasite cathepsin peptidases, we have shown that the peptidase inhibitors also play an important role in regulating host lysosomal-like cathepsin peptidases involved in the immune response to parasite infection [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cathepsins B and L (cysteine proteases) are secreted in high concentrations and often elicit humoral immune responses. These cathepsins, particularly F. hepatica cathepsin L1 (Q7JNQ9), have been the target of vaccination of ruminants against fascioliases [82]. A putative C. forsteri protease was classified as CfCL (Table 4) from sequence identity (44.68%) and a conserved active site (Cys 134 , His 281 , and Asn 301 ), which clusters with cathepsin L1 of schistosomes (Fig 4A).…”
Section: Plos Onementioning
confidence: 99%